2005
DOI: 10.1097/01.cad.0000171767.59187.c2
|View full text |Cite
|
Sign up to set email alerts
|

Single intratumoral injection of long-acting benzyl ester of D-penicillamine inhibits the growth of melanoma tumor in mice

Abstract: Using a murine model of melanoma we tested the effect of D-penicillamine administered in repetitive, daily injections, or as a single large dose injected either in saline or in a biodegradable polymer. We also studied the effect of a single intratumoral injection of benzyl-ester-D-penicillamine on the growth of the tumor. Daily injections of the drug or its administration in a polymer or benzyl-ester of D-penicillamine were all significantly inhibitory. The inhibitory effect manifested 4-5 days after injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…It has been demonstrated before that intratumoral injection of a long-acting benzyl ester of D-penicillamine inhibits the growth of melanoma tumors in mice [52]. In our murine SCID A375 melanoma model, significant inhibition of tumor growth was observed upon systemic administration of DP at very high daily doses (i.p.…”
Section: Discussionmentioning
confidence: 64%
“…It has been demonstrated before that intratumoral injection of a long-acting benzyl ester of D-penicillamine inhibits the growth of melanoma tumors in mice [52]. In our murine SCID A375 melanoma model, significant inhibition of tumor growth was observed upon systemic administration of DP at very high daily doses (i.p.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously reported on a novel D-pen-nanoparticle formulation for metal chelation therapy . Also, Chvapil et al recently reported on the synthesis of a hexyl-D-pen-ester that converted D-pen to a more lipophilic form (Log P = 1.61) , . The ester prodrug strategy for D-pen delivery could potentially have problems such as (i) the lack of protection of the critical thiol group and (ii) the slow rate of D-pen release from the lipophilic ester prodrug.…”
Section: Introductionmentioning
confidence: 99%